OPERATIONAL RISK ANALYSIS OF INDONESIAN SHARIA BANK OLD MOUNTAIN KCP - Wanda Khairani; Maria Kutbiah; Sarmiana Batubara; Adanan Murroh (Journal Of Sharia Banking, 2023)
Operational risk is one of the risks that must be faced by every financial institution, including Bank Syariah Indonesia (BSI) KCP Gunung Tua. Operational risk is faced by all banks because running a bank's business cannot be separated from the human factor, service procedures, administrative processes, and so on. With the emergence of operational risk, there must be causes. The operational risk can cause the bank to lose money which is caused by several factors, namely first, failure in internal processes related to procedural failures. Second, system failure, the main risk to operations due to the bank's increasing dependence on technology. Third, external events, external factors come from matters beyond the control of the bank which also affect the company's operational performance. This study used a qualitative research method with a descriptive approach, the data sources obtained were primary data and secondary data, which were obtained through interview methods, observation methods, documentation methods and data analysis methods.From the results of this study it can be seen that operational risks that occur at BSI KCP Gunung Tua occur due to internal risks such as incorrect checking of counterfeit money, human resource risks such as atk carried by customers, system risks, namely systems that are down and will always occur every year, risks law such as loss of customer guarantees, as well as external risks such as the Covid-19 disaster. The BSI KCP Gunung Tua continues to improve its risk management in order to reduce operational risks that occur. The method used by BSI KCP Gunung Tua to overcome operational risks that occur is by focusing on these 2 factors, optimizing controlling for all employees (internal) and also optimizing controlling for customers (external). It can be seen from the management that has been implemented quite well, it can be seen that the operational risk at BSI KCP Gunung Tua is now reduced. The current operational risk is only because the system is down and that is now only once a year. And the risk because of covid-19 has reduced.